2019
DOI: 10.1186/s40168-019-0748-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities of the house fly Musca domestica vary with geographical location and habitat

Abstract: House flies (Musca domestica) are widespread, synanthropic filth flies commonly found on decaying matter, garbage, and feces as well as human food. They have been shown to vector microbes, including clinically relevant pathogens. Previous studies have demonstrated that house flies carry a complex and variable prokaryotic microbiota, but the main drivers underlying this variability and the influence of habitat on the microbiota remain understudied. Moreover, the differences between the external and internal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 64 publications
6
88
3
3
Order By: Relevance
“…Our results also corroborated those from other studies, by demonstrating that house flies carry AMR and MDR bacteria in areas of livestock agriculture. A thorough assessment of the role flies play in harboring and disseminating bacteria, including AMR and MDR strains, and pathogens, is actively being investigated [8,10,12,[55][56][57], risk assessment models (e.g., [58]) can be enhanced by identifying and including variables related to bacterial source, the role of fly sex, environmental niche, fly dispersal patterns and farm management practices. Overall, we provide evidence of sex-specific effects on culturable bacterial load that includes AMR and MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also corroborated those from other studies, by demonstrating that house flies carry AMR and MDR bacteria in areas of livestock agriculture. A thorough assessment of the role flies play in harboring and disseminating bacteria, including AMR and MDR strains, and pathogens, is actively being investigated [8,10,12,[55][56][57], risk assessment models (e.g., [58]) can be enhanced by identifying and including variables related to bacterial source, the role of fly sex, environmental niche, fly dispersal patterns and farm management practices. Overall, we provide evidence of sex-specific effects on culturable bacterial load that includes AMR and MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Wild house flies harbor both pathogenic and nonpathogenic bacteria [6,8,9], including those that are antimicrobial resistant (AMR) [10,11]. Because flies associate with a wide variety of microbe rich sites across the landscape, it is not surprising that they harbor different microbial communities associated with the sites with which they interact [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, bees only accidentally bear S. cerevisiae , with only 1 occurrence over 21 reported cases ( Sandhu and Waraich, 1985 ; Lachance et al, 2003 ; Rosa et al, 2003 ; Daniel et al, 2013 ; Charron et al, 2014 ; Saksinchai et al, 2015 ). Conversely, S. cerevisiae has been found in a large portion of investigated flies, fruit flies, honey-bees, and wasps (29, 57, 20, and 71%, respectively) ( Phaff and Knapp, 1956 ; Batra et al, 1973 ; Sandhu and Waraich, 1985 ; Morais et al, 1993 , 1994 ; Rosa et al, 1994 ; Lachance et al, 1995 , 2003 , 2006 ; Suh et al, 2005 ; Nguyen et al, 2006 , 2007 ; Basukriadi et al, 2010 ; Goddard et al, 2010 ; Chandler et al, 2012 ; de Vega et al, 2012 ; Hamby et al, 2012 ; Stefanini et al, 2012 ; Freitas et al, 2013 ; Buser et al, 2014 ; Charron et al, 2014 ; Lam and Howell, 2015 ; Saksinchai et al, 2015 ; Batista et al, 2017 ; Deutscher et al, 2017 ; Jimenez et al, 2017 ; Piper et al, 2017 ; Quan and Eisen, 2018 ; Siavoshi et al, 2018 ; dos Santos et al, 2019 ; Meriggi et al, 2019 ; Park et al, 2019 ). A few possible scenarios could explain the higher occurrence of S. cerevisiae in these groups of insects: (i) they are more prone to visit human-related environments, such as wineries and vineyards, that are likely to host higher amounts of S. cerevisiae cells, (ii) they are more attracted by substrates inhabited by the budding yeast compared to other insects, (iii) diet and physical-chemical intestine conditions facilitate the housing of S. cerevisiae .…”
Section: Biogeography and Diffusionmentioning
confidence: 99%
“…In some cases, the differences reflect the phylogenetic relationships of the hosts (phylosymbiosis, e.g., [ 35 ]). On the other hand, since environment is a natural source of at least some portion of the microbiomes, the habitat and geographic location of the host may significantly affect microbiome composition (e.g., [ 36 39 ]). In triatomines, thirteen high throughput sequencing studies published since 2015 have indicated a wide range of factors that potentially influence their microbiomes.…”
Section: Introductionmentioning
confidence: 99%